The Effect of Maternal Class on Improving Mothers' Knowledge About Pregnancy, Labor, Postpartum, and Newborn in Pakan Kurai Village, Workingc Areac ff Guguakc Panjangc Community Healthc Center (HEALTH CARE: JURNAL KESEHATAN, 2025)
Introduction: Thec maternalc mortalityc rate in Indonesiac in 2023 isc 4,129. In West Sumatra in 2023, the number of maternal deaths was 118 cases. In the city of Bukittinggi in 2022, 1 case of maternal death was recorded. Pregnant women's classes are one of the promotive and preventive interventions in maternal health services and national efforts to reduce the Maternal Mortality Rate. Maternal class aim to increase pregnant women's knowledge about pregnancy, childbirth, postpartum and newborns. Objective: To determine the influence of maternal class on increasing mothers' knowledge about pregnancy, childbirth, postpartum and newborns. Method: Thisc study usedc a quasi-experimentalc design withc a pre-testc and post-testc approach withoutc a controlc group. Thec population of thisc study wasc pregnantc women. Thec sample consistedc of 32c respondents, thec sample wasc taken usingc the totalc samplingc technique. Data were collected through pre-test and post-test questionnaires. Data analysis included univariate analysis and bivariate analysis with the Wilcoxon signed ranks test. Results: Most respondents (87.5%) 20 people were aged 20-35 years, more than half of respondents (75%) 29 people were highly educated, more than half of respondents (56.2%) 18 people were employed, and most respondents (81.25%) 26 people were multigravida. There was an influence of the class of maternal at section 1 (p value 0.000), section 2 (p value 0.000), section 3 (p value 0.000) on increasing maternal knowledge about pregnancy, childbirth, postpartum and newborns. Conclusion: There is an influence of the maternal class women on increasing maternal knowledge about pregnancy, labor, postpartum and newborns in Pakan Kurai Village, Guguak Panjang Health Center Working Area, Bukittinggi City in 2025. It is recommended to conduct further research to determine the influence of the maternal class on her attitudes and behavior.